Expanding the Spectrum of Intraosseous Rhabdomyosarcoma: Correlation Between 2 Distinct Gene Fusions and Phenotype. (May 2019) - Agaram, Narasimhan P.; Zhang, Lei; Sung, Yun-Shao; Cavalcanti, Marcela S.; Torrence, Dianne; Wexler, Leonard; Francis, Glenn; Sommerville, Scott; Swanson, David; Dickson, Brendan C.; Suurmeijer, Albert J.H.; Williamson, Richard; et al.
Abstract : Primary intraosseous rhabdomyosarcomas (RMSs) are extremely rare. Recently 2 studies reported 4 cases of primary intraosseous RMS with EWSR1/FUS-TFCP2 gene fusions, associated with somewhat conflicting histologic features, ranging from spindle to epithelioid. In this study we sought to further investigate the pathologic and molecular abnormalities of a larger group of intraosseous RMSs by a combined approach using targeted RNA sequencing analysis and fluorescence in situ hybridization (FISH). We identified 7 cases, 3 males and 4 females, all in young adults, age range 20 to 39 years (median, 27 y). Three cases involved the pelvis, 2 involved the femur and 1 each involved the maxilla and the skull. Molecular studies identified recurrent gene fusions in all 7 cases tested, including: a novel MEIS1-NCOA2 fusion in 2 cases, EWSR1-TFCP2 in 3 cases, and FUS-TFCP2 gene fusions in 1 case. One case showed a FUS gene rearrangement, without a TFCP2 gene abnormality by FISH. The MEIS1-NCOA2 –positive cases were characterized by a more primitive and fascicular spindle cell appearance, while the EWSR1/FUS rearranged tumors had a hybrid spindle and epithelioid phenotype, with more abundant eosinophilic cytoplasm and mild nuclear pleomorphism. Immunohistochemically, all tumors were positive for desmin and myogenin (focal). In addition, 4 tumors with TFCP2 -associated gene fusions also coexpressed ALK and cytokeratin. In conclusion, our results suggest a high incidence of gene fusions in primary RMSs of bone, with 2 molecular subsets emerging, defined by either MEIS1-NCOA2 or EWSR1/FUS-TFCP2 fusions, showing distinct morphology and immunophenotype. Additional studies with larger numbers of cases and longer follow-up data are required to definitively evaluate the biological behavior of these tumors and to establish their relationship to other spindle cell RMS genetic groups. Abstract : Supplemental Digital Content is available in the text.